Individual heterogeneity determines sex differences in mortality in a monogamous bird with reversed sexual dimorphism. (10th May 2017) - Colchero, Fernando; Aliaga, Alix Eva; Jones, Owen R.; Conde, Dalia A.
Summary: Sex differences in mortality are pervasive in vertebrates, and usually result in shorter life spans in the larger sex, although the underlying mechanisms are still unclear. On the other hand, differences in frailty among individuals (i.e. individual heterogeneity), can play a major role in shaping demographic trajectories in wild populations. The link between these two processes has seldom been explored. We used Bayesian survival trajectory analysis to study age‐specific mortality trajectories in the Eurasian sparrowhawk ( Accipiter nisus ), a monogamous raptor with reversed sexual size dimorphism. We tested the effect of individual heterogeneity on age‐specific mortality, and the extent by which this heterogeneity was determined by average reproductive output and wing length as measures of an individual's frailty. We found that sex differences in age‐specific mortality were primarily driven by the differences in individual heterogeneity between the two sexes. Females were more heterogeneous than males in their level of frailty. Thus, a larger number of females with low frailty are able to survive to older ages than males, with life expectancy for the least frail adult females reaching up to 4·23 years, while for the least frail adult males it was of 2·68 years. We found that 50% of this heterogeneity was determined by average reproductive output and wing length in both sexes. For both, individuals with high average reproductive output had also higher chances to survive. However, the effect of wing length was different between the two sexes. While larger females had higher survival, larger males had lower chances to survive. Our results contribute a novel perspective to the ongoing debate about the mechanisms that drive sex differences in vital rates in vertebrates. Although we found that variables that relate to the cost of reproduction and sexual dimorphism are at least partially involved in determining these sex differences, it is through their effect on the level of frailty that they affect age patterns of mortality. Therefore, our results raise the possibility that observed differences in age‐specific demographic rates may in fact be driven by differences in individual heterogeneity. Abstract : The authors found that sex differences in mortality were primarily driven by differences in the variance in individual frailty in a sexually dimorphic species. Furthermore, they show that these differences are partly explained by lifetime reproductive effort and wing length, both uncorrelated measures of individual quality.